Impact of ISO 9001: 2008 in the Faculty of Engineering of the National University of Chimborazo- Ecuador as part of the Quality Management System - Salazar Yépez, Wilfrido (2017)
The purpose of this article is to determine the impact of the ISO 9001: 2008 standard on the quality management system at the Faculty of Engineering at the National University of Chimborazo, Ecuador. This research is the result of a field work, where an analysis of the information collected was carried out, through surveys validated by Cronbach's alpha. The sample is of 200 students, with a level of significance of 95%, they were applied to the students in a random way, the results show that the impact is good.